2014
DOI: 10.1159/000363062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <smlcap>L</smlcap>-Carnitine on High Glucose-Induced Oxidative Stress in Retinal Ganglion Cells

Abstract: Background: Oxidative stress plays a role in diabetic retinopathy. L-Carnitine is an endogenous mitochondrial membrane compound. Objective: To elucidate the protective effects of L-carnitine on high glucose-induced oxidative stress in retinal ganglion cells (RGCs). Methods: Hoechst 33258 staining was used to estimate cell loss. Mitochondrial function was predicted by mitochondrial membrane potential (ΔΨm) measurement. The expression of apoptosis-related protein was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
22
0
5
Order By: Relevance
“…The results revealed that RPE proliferative ability is inhibited by glucose in a dose dependent manner. In addition, ROS generation is also induced by glucose in a dose dependent manner (Figure 1J-K), which is in accordance with the previous studies [34, 35].…”
Section: Discussionsupporting
confidence: 92%
“…The results revealed that RPE proliferative ability is inhibited by glucose in a dose dependent manner. In addition, ROS generation is also induced by glucose in a dose dependent manner (Figure 1J-K), which is in accordance with the previous studies [34, 35].…”
Section: Discussionsupporting
confidence: 92%
“…The generation of ROS under high glucose stress conditions has been established in many cell types [ 27 , 28 ]. When the ROS level exceeds the capacity of the antioxidant defense system, ROS initiates chain reactions by oxidizing cellular macromolecules like lipids and proteins, which in turn interrupts cellular activities, ultimately causing apoptosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that Hax-1 interacts with apoptosis-associated proteins, including HtrA2, protease-activated receptor 1 (Par1), caspase-3, caspase-9 or Bcl-2-associated X protein (8,(21)(22)(23). Numerous studies have demonstrated that the activation of caspase-3 was the key effector of RGC apoptosis following ONC (24)(25)(26). Previously, Hax-1 has been identified as a new substrate of caspase-3, which prevents apoptosis by inhibiting the catalytic activation of caspase-3 (27).…”
Section: Discussionmentioning
confidence: 99%